Learning Management with Concept Mapping on Digestive System to Enhance Systems Thinking and Learning Achievement for Grade 11th Students - Plasom, Piyapan; Passago, Somsanguan (Ratchaphruek Journal, 2021)
The research aimed to study the learning management by using concept mapping to enhance system thinking. The purposes of this study were: 1) To compare students’ systems thinking before and after receiving the learning management with concept mapping; 2) To compare the students’ learning achievement after learning with the 70 percent criteria; and 3) To study correlation between students’ systems thinking and their learning achievement after learning. The 39 sample from cluster random sampling were grade 11th students, in the second semester of the 2020 academic year, at Anukoolnaree School, Kalasin Province. The research instruments were lesson plans, the system thinking test, and the learning achievement test. Data were analyzed by mean, percentage, standard deviation, t-test, and multiple correlation analysis. The research results were found that; 1) Students’ systems thinking were significantly higher than before the learning at the .05 level. 2) Students’ learning achievement were significantly higher than the 70 percent criteria at the .05 level. 3) The students’ systems thinking and learning achievements revealed the positive correlation at .05 significant level. The system thinking could be supported the learning achievement on digestive system of grade 11th students up to 90 percent.